2020
DOI: 10.1021/acsami.0c04199
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Induced Structural and Morphological Evolutions in Nickel Vanadium Oxide Hydrate Nanobelts Enabling Fast Transport Kinetics for High-Performance Zinc Storage

Abstract: Suitable intercalation cathodes and fundamental insights into the Zn-ion storage mechanism are the crucial factors for the booming development of aqueous zinc-ion batteries. Herein, a novel nickel vanadium oxide hydrate (Ni0.25V2O5·0.88H2O) is synthesized and investigated as a high-performance electrode material, which delivers a reversible capacity of 418 mA h g–1 with 155 mA h g–1 retained at 20 A g–1 and a high capacity of 293 mA h g–1 in long-term cycling at 10 A g–1 with 77% retention after 10,000 cycles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 62 publications
0
33
1
Order By: Relevance
“…where k 1 and k 2 are adjustable parameters, and k 1 v and k 2 v 1/2 behave as surface-controlled and diffusion-controlled parameters, respectively. 52,53 According to Fig. 4( j)-(l), the proportion of pseudocapacitive contribution is 94.7% for the fresh electrode, and then the value becomes 88.1% after 100 cycles, which is 9.58% for the electrode after 600 cycles at an equal scan rate of 1 mV s −1 .…”
Section: (D)-(f ) the Corresponding Kinetic Informationmentioning
confidence: 96%
“…where k 1 and k 2 are adjustable parameters, and k 1 v and k 2 v 1/2 behave as surface-controlled and diffusion-controlled parameters, respectively. 52,53 According to Fig. 4( j)-(l), the proportion of pseudocapacitive contribution is 94.7% for the fresh electrode, and then the value becomes 88.1% after 100 cycles, which is 9.58% for the electrode after 600 cycles at an equal scan rate of 1 mV s −1 .…”
Section: (D)-(f ) the Corresponding Kinetic Informationmentioning
confidence: 96%
“…Another hydrated nickel vanadate Ni 0.25 V 2 O 5 ·0.88H 2 O (NiVO) nanobelt cathode prepared by hydrothermal method was also reported by Feng et al [ 154 ] NiVO cathode with a double‐layered structure (Figure 18j) displayed a high specific capacity of 418 mAh g −1 at 0.1 A g −1 with initial coulombic efficiency of 99% and retained a specific capacity of 155 mAh g −1 at 20 A g −1 . This cathode retained 226 mAh g −1 (77% capacity retention) after 10 000 cycles at a current density of 10 A g −1 .…”
Section: Electrolyte Modificationsmentioning
confidence: 97%
“…In addition, many other V-based cathode materials delivered a specific capacity greater than 200 mAh g À1 at current densities ranging from 10 and 30 A g À1 . Some examples are V 2 O 5 / graphene, [129] hydrated V 2 O 5 , [132,133] transition metal-intercalated V 2 O 5 (Cu, Ni), [146,154] NH 4 V 4 O 10 , [157] and V 6 O 13 (Mn-doped, hydrated). [174,179] The majority of these materials were prepared by hydrothermal method, which is a simpler method of preparation compared with other techniques shown in Table 2.…”
Section: Layered V 2 O 5 -Based Cathodes: Summary and Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…In a related study, Feng et al reported ‘structure‐evolving’ Ni 0.25 V 2 O 5 ·0.88H 2 O (NiVO) nanobelts (Figure 8d) as high‐performance cathode materials for ZIBs in Zn(CF 3 SO 3 ) 2 electrolyte. [ 83 ] NiVO material was formed in monoclinic crystal system where edge‐sharing bilayer VO 6 octahedrons were joined by NiO 6 octahedrons as depicted in Figure 8e. Each NiO 6 octahedron was also bound to four structural water units.…”
Section: Vanadium‐containing Materialsmentioning
confidence: 99%